OR28-01 Constitutive Activation of NRF2 Antioxidant Response Leads to Age-Dependent Goiter and Compensated Hypothyroidism in Male Mice - Chartoumpekis, Dionysios (J Endocr Soc, 2020)
Background: Familial non-toxic multinodular goiter (MNG) is a rare disease. KEAP1 gene (Kelch-like ECH-associated protein 1) that encodes the main inhibitor of nuclear factor erythroid 2-related transcription factor 2 (Nrf2), a central mediator of antioxidant responses, has been found to be one of the mutated genes that lead to familial MNG. The proposed association of KEAP1 with familial MNG is based on only two loss-of-function mutations in respective Japanese families, only one of which included proper phenotyping and demonstration of co-segregation of phenotype and mutation. To date, there is no experimental evidence from model organisms to support that decreased Keap1 levels can cause goiter. Hypothesis: We hypothesized that enhanced Nrf2 signaling induced by loss of Keap1 function in mice can lead to goiter. Methods: To this end, male Keap1 hypomorphic C57BL/6J mice that express ~80% less Keap1 in their tissues (Keap1 knockdown mice:“Keap1KD”) were studied at 3 and 12 months of age and compared to wild-type mice (WT). Plasma, thyroids and pituitary glands were collected for assessment of thyroid function by radioimmunoassays and for histology as well as gene and protein expression by quantitative PCR and immunoblotting respectively. Results: Keap1KD showed diffuse goiter that began to develop in early adult life and became highly prominent at the age of 12 months when the thyroids of Keap1KD were 6-fold heavier than WT. Histomorphometry assessment of thyroids showed that Keap1KD had ~3-fold larger follicle area and colloid compartment but no thyroid nodules or hyperplasia was detected. Keap1KD also showed primary hypothyroidism already in early adult life that was eventually well-compensated over time by increased TSH levels (at age of 12 months: WT TSH=47.7±9.1 mU/L, Keap1KD TSH=460±74 mU/L). This was also reflected in the pituitary gland of Keap1KD where Tshb mRNA was ~3-fold higher than WT. Despite a known stimulatory effect of Nrf2 on Tg gene transcription and Tg protein abundance, these measures were decreased in the thyroid of Keap1KD mice. No clear patterns were observed in the expression profiles of other thyroid hormone synthesis-specific factors, such as Duox1, Duoxa1, Duox2, Duoxa2, Tpo, Nis, Dio1, Dio2, Dehal1 mRNA levels, with the exception of Tg-processing and Tg-degrading cathepsins, including an increase in mature forms of cathepsins D, L and S. Conclusions: Keap1KD mice showed age-dependent diffuse goiter and compensated hypothyroidism. The precise mechanism accounting for the thyroidal phenotype remains to be elucidated, but it may involve enhanced Tg solubilization and excessive lysosomal Tg degradation. This study unravels novel roles of the druggable Keap1/Nrf2 pathway in thyroid function and economy. Subclinical hypothyroidism in Keap1KD mice may have broader implications regarding their use in metabolic research.